Evaluation Time as Most Effective Factor in Success of Thrombolysis with Streptokinase in Patients with Acute STEMI During COVID 19 Pandemic (Medical Forum Monthly, 2022)
Objective: The objective of this study to evaluate time as most effective factor in success of thrombolysis with streptokinase in patients with acute STEMI during covid 19 pandemic.Study Design: Prospective observational studyPlace and Duration of Study: This study was conducted at the Kashmir institute of Cardiology, Mirpur Azad Jammu and Kashmir, from April 2020 to December 2020 for a period of nine months.Materials and Methods: Patients presenting in emergency department with Acute STEMI were included, patients were analyzed via history, clinical examination and ECG findings of Acute STEMI.Results: Total of 110 patients were included in study. 80% (88) patients were male and 20%(22) patients were female. Which shows increase in the number of female patients with acute STEMI In this study we have tried to compare ECG based success criterion with international data and our data back in 2016. During the study we found successful thrombolysis around 45% during covid 19 pandemic.Conclusion: Time from onset of symptoms of Acute STEMI and start of streptokinase treatment was proven to be most effective method to improve the chances of success of streptokinase treatment and reduce mortality in such patients, as regard to my previous study in 2016 in same institute success of thrombolysis was markedly reduced with streptokinase during the covid 19 pandemic using the same treatment parameters.